Perlindungan Hukum Pada Anak Korban Kekerasan Seksual Yang Dilakukan Oleh Oknum Pemilik Pondok Pesantren Di Bandung - Komala Sari; Taun Taun (Legal Spirit, 2022)
Children are gifts that have been given by God to always be guarded and protected. Children are referred to as the young generation who play a role and become the nation's successor, and their physical growth and development must be guaranteed. The number of cases of violence against minors today is not only in open society but can also occur in Islamic boarding schools. This writing aims to provide information on legal protection against sexual violence against minors and the factors that cause sexual violence by unscrupulous owners of Islamic boarding schools in Bandung. The research method used is the method of writing normative law. The results of the study can be said that the important role of parents, society and government in terms of child protection has also been regulated through positive law in Indonesia, both for prevention and for what is currently stated in written form which includes people who commit crimes with criminal threats. The occurrence of sexual violence in Islamic boarding schools is the result of the power factor.